2019
DOI: 10.1016/j.ebiom.2019.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic homeostasis and resilience of the complement system in health and infectious disease

Abstract: Background The complement system is a central component of the innate immune system. Constitutive biosynthesis of complement proteins is essential for homeostasis. Dysregulation as a consequence of genetic or environmental cues can lead to inflammatory syndromes or increased susceptibility to infection. However, very little is known about steady state levels in children or its kinetics during infection. Methods With a newly developed multiplex mass spectrometry-based me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 53 publications
2
24
2
Order By: Relevance
“…In many cases, we observed an additional reduction through functional coupling of complement factors within the pathways down-or upstream of the deficient protein, although not fully depleted. That other complement proteins were not totally depleted, especially when a complement inhibitor is deficient, emphasises the previously observed resilience of the complement system 19 even in severe complement deficiencies.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…In many cases, we observed an additional reduction through functional coupling of complement factors within the pathways down-or upstream of the deficient protein, although not fully depleted. That other complement proteins were not totally depleted, especially when a complement inhibitor is deficient, emphasises the previously observed resilience of the complement system 19 even in severe complement deficiencies.…”
Section: Discussionsupporting
confidence: 65%
“…The development, accuracy and reproducibility of the assay have been established previously. 19 The assay was further improved by implementing pure (> 98%) instead of crude (> 50%) heavy isotopelabelled internal peptide standards for absolute quantification. For clinical implementation, the assay needs additional diagnostic validation, according to clinical mass spectrometry standards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study, and a number of others, have shown that terminal pathway proteins comprising the MAC (C6-C9) are significantly lower in pre-term and full term infants, as are proteins of the classical and alterative pathways [reviewed in ( 82 )]. In addition, a recent study determined that the blood levels of C9 in children less than one year of age were significantly lower compared to adults, and adult levels were reached between two and eighteen years of age ( 83 ). These studies indicate that sMAC levels in are lower in children, in part, because the concentration of proteins that compose the MAC are lower.…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that C3 and C4 consumption, as well as C5b-9 deposition on HEp-2 cells co-cultured with SLE serum and HEp-2 cells, decreased significantly following treatment with IgG4 autoantibodies (but not control IgG4) in a concentrationdependent manner. It has been confirmed that complement abnormalities (4) and the function of complement molecules influence IC processing and transportation (7,42). In addition, the ICs that can effectively activate complement molecules show greater pathological significance, with significantly more ICs found in SLE patients that were closely associated with SLE-related disease activities (43).…”
Section: Discussionmentioning
confidence: 94%